2022
DOI: 10.1186/s13229-022-00535-0
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual heterogeneity of functional brain networks in children with autism spectrum disorder

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder with considerable clinical heterogeneity. This study aimed to explore the heterogeneity of ASD based on inter-individual heterogeneity of functional brain networks. Methods Resting-state functional magnetic resonance imaging data from the Autism Brain Imaging Data Exchange database were used in this study for 105 children with ASD and 102 demographically matched typical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…The joint recurrence quantification technique was used to quantify the synergy of brain configuration dynamics in ASD, and then clustered for subtyping based on the quantization results. ASD subtypes with altered and heterogeneous FC patterns were reported in previous studies (Chen et al, 2019; Guo, Zhai, et al, 2022; Reardon et al, 2022). And previous studies have found that there are 2–4 subtypes of ASD, therefore we predict that ASD can be divided into 2–4 subtypes with heterogeneous and atypical synergy of SN, that is, ASD can be divided into subtypes with different patterns of functional interaction of SN (Guo, Zhai, et al, 2022; Hong et al, 2018; Hrdlicka et al, 2005).…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…The joint recurrence quantification technique was used to quantify the synergy of brain configuration dynamics in ASD, and then clustered for subtyping based on the quantization results. ASD subtypes with altered and heterogeneous FC patterns were reported in previous studies (Chen et al, 2019; Guo, Zhai, et al, 2022; Reardon et al, 2022). And previous studies have found that there are 2–4 subtypes of ASD, therefore we predict that ASD can be divided into 2–4 subtypes with heterogeneous and atypical synergy of SN, that is, ASD can be divided into subtypes with different patterns of functional interaction of SN (Guo, Zhai, et al, 2022; Hong et al, 2018; Hrdlicka et al, 2005).…”
Section: Introductionsupporting
confidence: 51%
“…In DSM V, the diagnostic criteria for ASD, Autistic Disorder, Asperger's Disorder, and Pervasive Developmental Disorder are unified as ASD, which shows that ASD cannot be simply divided into Autistic Disorder, Asperger's Disorder, or Pervasive Developmental Disorder (American Psychiatric Association, 2013). ASD has complex neural mechanisms, and the complex neural mechanisms are associated with heterogeneous symptoms so that the neurological subtypes of ASD need to be investigated from more perspectives (Guo, Zhai, et al, 2022; van Rentergem et al, 2021). The present study is consistent with the results of previous ASD subtype studies, where ASD could be classified into 2–4 subtypes (Guo, Zhai, et al, 2022; Hong et al, 2018; Hrdlicka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, based on the inter-individual deviation of functional connectivity (IDFC), Xiaonan Guo and colleagues found two ASD subtypes, each with a different level of social communication deficits and confined and repetitive behaviors ( 64 ). Ada J S Chan and his colleagues discovered that distinct genetic subtypes of ASD can enable the prediction of developmental outcomes ( 65 ).…”
Section: Discussionmentioning
confidence: 99%